Reused N95 Face Masks Performance: Effect of Gamma Irradiation Method on Residual Bioburden and Functional Material Resistance - Ade Lestari Yunus; Akhmad Rasyid Syahputra; Rizka Fitriana; Deswita; Bimo Saputro; Muhamad Yasin Yunus; Hanna Yasmine; Devita Tetriana; Irawan Sugoro; Darmawan Darwis (International Journal of Technology)
Due to the pandemic of Covid-19, the use of face masks has been very intense. There is a need for an innovative solution to enable reuse of face masks that have been exposed to viruses or bacteria. Face mask sterilization by gamma irradiation could be one of the solutions. However, to ensure that the quality of the sterilized mask is still at a satisfactory level, chemical, thermal, and mechanical tests need to be conducted. Firstly, microbial analysis or bioburden is carried out. The effective dose for reducing microbes is found 23.2 kGy. These results are reinforced by several functional tests. FTIR measurement found no crucial functional group changes from polyester and polypropylene to masks. At 15 kGy and 25 kGy absorbed gamma irradiation, the elongation tensile strength of the mask slightly increased by 1.3 and 0.8 points higher than the initial. The tensile strength value decreased from 3.02 MPa to 2.27 MPa and 2.53. MPa for 15 kGy and 25 kGy. After several sterilization techniques, DSC curves showed melting point of polyester and polypropylene do not significant changes. SEM-EDS analysis show no presence of bacteria of viruses 0% mass of nitrogen at each of several methods of sterilization. After gamma irradiation, the morphology of polypropylene surfaces became slightly flawed, spaced, and fractured.